STRATEGI PENCEGAHAN MONEY POLITIC MELALUI KAMPUNG ANTI POLITIK UANG DAN HOAKS - Ikang Putra Anggara; Nur Rois; Nissa Wahida Kusuma (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
Money politics is realized that it has become massive and has become a serious problem in the process of holding general elections. To realize a more qualified and responsible election, various efforts and strategies were carried out, one of which was by forming an Kampung Anti Politik Uang dan Hoaks in Air Gading Village, Baturaja Barat District, Ogan Komering Ulu Regency. The research method used is a qualitative method. The data in this study were collected through observation, interviews, and documentation, which involved 11 (eleven) informants. The strategies carried out through the Kampung Anti Politik Uang dan Hoaks in Air Gading Village, Baturaja Barat District, Ogan Komering Ulu Regency, among others, first, providing political education to community leaders, religious leaders, and youth leaders about the prevention, impact, and sanctions on money politics practices. by Bawaslu of Ogan Komering Ulu Regency. Second, to encourage participatory supervision of the people of Air Gading Village, Baturaja Barat District, Ogan Komering Ulu Regency.